(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
The genesis of the European Union (EU) is focused on the regional integration purpose which aims to assure peace. Although various impulses have been introduced in order to establish a collective external policy, this one was confronted with somewhat diverging national perspectives. As the EU shares common values in the issues of democracy, human rights and state of law, it is recognized as an essentially humanitarian power that uses soft power tools in its external relations. The application of restrictive measures such as restrictions concerning political and diplomatic nature, admission and circulation, and trade and financial nature, has been used with the goal of changing behaviours or policies of states, entities or individuals who break the principles of international or humanitarian law. The paper aims to articulate the EU sanction regimes, as a result of a gradual legal framework that reached the EU Global Regime of Sanctions in Human Rights, with the adoption of strategic action plans in human rights and democracy.